In vitro Analysis of O-Antigen-Specific Bacteriophage P22 Inactivation by Salmonella Outer Membrane Vesicles - Stephan, Mareike S.; Broeker, Nina K.; Saragliadis, Athanasios; Roos, Norbert; Linke, Dirk; Barbirz, Stefanie (Frontiers in Microbiology, 2020)
Bacteriophages use a large number of different bacterial cell envelope structures as receptors for surface attachment. As a consequence, bacterial surfaces represent a major control point for the defense against phage attack. One strategy for phage population control is the production of outer membrane vesicles (OMVs). In Gram-negative host bacteria, O-antigen specific bacteriophages address lipopolysaccharide (LPS) to initiate infection, thus relying on an essential outer membrane glycan building block as receptor that is constantly present also in OMVs. In this work, we have analyzed interactions of Salmonella (S.) bacteriophage P22 with OMVs. For this, we isolated OMVs that were formed in large amounts during mechanical cell lysis of the P22 S. Typhimurium host. In vitro, these OMVs could efficiently reduce the number of infective phage particles. Fluorescence spectroscopy showed that upon interaction with OMVs, bacteriophage P22 released its DNA into the vesicle lumen. However, only about one third of the phage P22 particles actively ejected their genome. For the larger part, no genome release was observed, albeit the majority of phages in the system had lost infectivity towards their host. With OMVs, P22 ejected its DNA more rapidly and could release more DNA against elevated osmotic pressures compared to DNA release triggered with protein-free LPS aggregates. This emphasizes that OMV composition is a key feature for the regulation of infective bacteriophage particles in the system.